(untitled) (Journal of Applied Learning and Teaching, 2022)
This article presents a quantitative analysis of the determinants of student scores on a standardized mathematics assessment in Cameroon, a sub-Saharan African country with Francophone and Anglophone school systems. Using the mathematics component of the 2014 Programme d’Analyse des Systèmes Educatifs de la CONFEMEN survey, we examined the importance of community, school and classroom resourcing, teacher attributes, student characteristics, and family circumstances. Our results generally suggest that both school and family factors play a role in determining student achievement in mathematics. We found that student mathematics scores are highest for males, younger students, non-grade repeaters, urban students, when teachers are better resourced, and when students come from well-off family situations with parents who are able to read. Analyses of sub-samples and an expanded sample (with interaction effects) generally corroborate these results but also reveal further differences, including between the Francophone and Anglophone school systems. Finally, the results indicate that the kindergarten program is not systematically associated with better mathematics test scores, suggesting that this policy may need further study and modification.